Intellectual capital and social performance of Islamic banks in Indonesia and Malaysia: the moderating role of sharia supervisory boards - Pratama, Bima Cinintya; Amrizah Kamaluddin,; Shukriah Saad, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The purpose of this study is to investigate the relationship between Intellectual Capital (IC) and Social Performance and to further examine whether Sharia Supervisory Boards (SSB) moderate this relationship. This study employed a longitudinal sample of Islamic banks in two countries leading Islamic banking industries in the south-east Asia region, Malaysia and Indonesia, with a sample of 31 Islamic banks during the period 2008-2020. Panel data regression model analysis was applied to test the study research hypotheses. The findings revealed that IC has a positive impact on the social performance of Islamic banks, demonstrating that greater utilization of IC leads to improved social performance. SSB meeting frequency has a positive impact on the social performance of Islamic banks, indicating that the more active the boards are, the more SSB can perform the social performance. Meanwhile, the gender diversity of SSB members has does not influence Islamic banks’ social performance. On the moderating role of SSB aspects, which are SSB meeting frequencies representing SSB activities in monitoring and SSB gender diversity, both proven to strengthen the relationship between IC and Islamic banks’ social performance. Overall, this research contributes to a better understanding of the impact of IC and SSB governance in improving Islamic banks’ social performance functions. This study implies that Islamic banks should be more aware of their intellectual capital resources and the monitoring role of SSB so that the Islamic banks can perform their social functions more optimally.